EFFECTIVENESS OF INTRAVENOUS VS RECTAL ACETAMINOPHEN FOR PAIN MANAGEMENT IN POST OPERATIVE NEONATES (Journal of Medical & Health Sciences Review, 2024)
Background: Adequate postoperative analgesia in neonates remains challenging due to pharmacokinetic variations and limited analgesic options. This study compared the efficacy of intravenous and rectal routes of acetaminophen administration for postoperative pain management in term neonates.Methods: A single-blind randomized controlled trial enrolled 64 term postoperative neonates (≥37 weeks gestation, birth weight ≥2.5 kg) requiring analgesia for ≥12 hours. Participants were randomly allocated to receive acetaminophen 15 mg/kg intravenously (Group A, n=32) or rectally (Group B, n=32) every 6 hours for a maximum of 48 hours. Demographic characteristics included age, gender, and weight. Primary outcomes assessed were rescue analgesia requirement and time to rescue analgesia. Secondary outcomes included pain score reduction using the Neonatal Pain, Agitation and Sedation Scale (NPASS).Results: Baseline demographic characteristics were comparable between groups. Rescue analgesia was required in 54.7% of the total study population. Notably, only 37.5% of neonates in Group A required rescue analgesia compared to 71.9% in Group B (p = 0.012). The mean time to rescue analgesia was significantly longer in Group A (4.82 ± 0.57 hours) versus Group B (3.18 ± 0.66 hours; p < 0.001). Intravenous acetaminophen produced a greater mean pain reduction of 6.09 ± 1.48 points compared to 4.50 ± 1.48 points with rectal administration (p < 0.001).Conclusion: Intravenous acetaminophen demonstrated superior analgesic efficacy compared to rectal administration in postoperative term neonates, with reduced rescue analgesia requirements and greater pain score reduction. These findings suggest that the intravenous route may be preferred for postoperative analgesia in term neonates when vascular access is available.